Analysis of the Needs of Local History LKPD the Berau Kingdom in History Learning at Public Senior High School 10 Berau - Ratu Rahmini; Rhoma Dwi Aria Yuliantri; Awanis Akalili (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This study aims to describe students' prior knowledge of the local history of the Berau Kingdom, analyze the need for student worksheets (LKPD) based on that local history, and depict the actual conditions of local history learning in Class XA of SMA Negeri 10 Berau. The study employed a descriptive qualitative approach with a focus on needs analysis. The research subjects were 27 students of Class XA selected through purposive sampling. Data were collected through a four-point Likert-scale questionnaire supplemented by open-ended questions and classroom observations, and were then analyzed using percentage techniques and descriptive qualitative analysis. The results revealed three key findings. First, students' prior knowledge of the Berau Kingdom's local history was in the low to moderate category, with positive response rates not exceeding 48.1%, the lowest being recognition of important historical figures (37.0%). Second, a significant instructional gap was identified: only 25.9% and 22.2% of students considered the existing textbooks and worksheets to cover Berau Kingdom's local history. In comparison, 63.0% expressed a need to study it, and 66.7% believed that a locally based LKPD would improve their understanding. Third, classroom observation confirmed that history learning remained entirely centered on national textbooks, with all aspects of local history integration unfulfilled. However, students showed genuine enthusiasm when local contexts were mentioned. These findings constitute valid baseline data as a scientific foundation for developing an LKPD based on the local history of the Berau Kingdom in subsequent research.